The Directorate General of Pesantren: Structural Opportunities and Policy Challenges - Abdul Mukti Bisri; Zakariyah Zakariyah (Islamic Education Management Study Program, Faculty of Tarbiyah, Sunan Drajat Islamic Boarding School Institute, Lamongan, East Java, Indonesia., 2026)
The establishment of the Directorate General of Pesantren under Presidential Regulation No. 18 of 2026 represents a major institutional reform in Indonesia’s religious education governance. From a public policy perspective, institutional restructuring serves as a governance instrument to strengthen policy capacity, coordination, and implementation effectiveness while addressing long-standing fragmentation in pesantren administration (Dunn, 2003; Howlett, Ramesh, & Perl, 2020). With more than 42,000 registered pesantren serving millions of santri, this reform reflects the growing strategic role of pesantren within the national education system (Ministry of Religious Affairs of the Republic of Indonesia, 2025). This study employs a qualitative library research design using purposively selected policy documents, government regulations, academic books, and peer-reviewed journal articles. Data were analyzed through qualitative content analysis, thematic coding, and comparative policy analysis, while source triangulation ensured the credibility of the findings. The results suggest that the Directorate General creates opportunities for stronger institutional coordination and policy integration but may also generate challenges related to bureaucratic expansion, overlapping authority, fiscal inequality, and institutional adaptability. This study argues that policy effectiveness depends not merely on organizational restructuring but on governance quality, operationalized through adaptive decision-making, participatory stakeholder engagement, and equitable resource allocation and policy implementation across diverse categories of pesantren.